Poly(ethylene glycol)-Thioxanthone Prepared by Diels-Alder Click Chemistry as One-Component Polymeric Photoinitiator for Aqueous Free-Radical Polymerization - Akat, Hakan; Gacal, Burcin; Balta, Demet Karaca; Arsu, Nergis; Yagci, Yusuf (WILEY, 2010)
Novel water-borne macrophotoinitiator containing thioxanthone (TX) end group was successfully synthesized by using Die Is Alder (DA) [4 + 2] click chemistry strategy. For this purpose, thioxanthone-anthracene (TX-A) and maleimide end-functionalized poly(ethylene glycol) (PEG-MI) were reacted in toluene at reflux temperature for 48 h. The final polymer (PEG-TX) and the intermediates were characterized in detail by spectral analysis. PEG-TX possesses absorption characteristics similar to the parent TX. The one-component photoinitiating nature of the photointiator was demonstrated by photopolymeization of several hydrophilic vinyl monomers, such as acrylic acid, acrylamide, 2-hydroxyethyl acrylate, and 1-vinyl-2-pyrrolidone. (C) 2010 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 48: 2109-2114, 2010
Keywords: aqueous free-radical polymerization; click chemistry; Diels Alder cycloaddition; macrophotoinitiator; photopolymerization; thioxanthone; IN-CHAIN THIOXANTHONE; COINITIATOR AMINE; 1,3-DIPOLAR CYCLOADDITIONS; BLOCK-COPOLYMERS; TERMINAL ALKYNES; BENZOPHENONE; AZIDES; ATRP; Polymer Science